PENGARUH RELIGIUSITAS DAN PROFIT MARGIN TERHADAP TINGKAT PERKEMBANGAN JUMLAH NASABAH DI BANK SYARIAH MANDIRI GARUT - Yasir Muharram Fauzi (Masoem University, 2017)
Various previous studies show different results. Religiosity/emotional variables, for example, turn out to be the main factor of public preference for choosing Islamic banks for the people of Central Java. While for the people of West Java and East Java was religiosity / religiosity does not become the main factor of choice and preference for the utilization of sharia banks. On the other hand shows that the growth of DPK in 2004 of sharia banks in Central Java reached 247.81% exceeds the national level of only 106.55%. On average, the growth of Islamic banking DPK in Central Java between 2004 and 2009 was 74.87%. While the national level between 2004 to 2009 only ranged 45.14%. Consumer preferences according to the concept of sharia are not based on the spirit of the value of rationalism and utilitarianism, but based on the value of